Handbook of polymer degradation - Hamid, S. Halim; Amin, Mohamed B.; Maadhah, Ali G. (Environmental science and pollution control series, 1992)
This useful reference provides up-to-date coverage, from both the engineering and scientific viewpoints, of the most recent findings in the expanding field of polymer degradation and stabilization - including areas in which polymers have only recently been used and detailed information has not previously been available. as advanced material for more in-depth study, Handbook of Polymer Degradation: introduces new data on the effects of increased UV radiation on polymers and discusses how to decrease those effects; considers artificially accelerated weathering and its relationship with natural weather; examines weathering degradation of polyethylene with the relevant experimental results; emphasizes the environmental aspects and waste management of polymers; and combines insights on the environmental toxicology of plastics with a survey of current legislative issues. different parts of the world, Handbook of Polymer Degradation is an essential reference for chemical, polymer, environmental, pollution control, mechanical, and materials scientists and engineers; chemists; environmental regulators and policy makers; and upper-level undergraduate and graduate students in these disciplines.